Think and educate in the love and the sexuality to teenagers (Journal of Parents and Teachers, 2015)
Love and sexuality are two pending subjects in adolescent development and maturity that require special care in his formation, dialogue and expression. Parents and educators should care semantics, syntax and grammar of this wonderful affective-sexual language to accompany them in this way
Keywords: Sex education; Affectivity; Sexual Morality; Sexual and Reproductive Health